THE RELEVANCE OF LIFELONG LEARNING TO SELF-RELIANCE: THE ROLE OF SCIENCE, TECHNOLOGY AND MATHEMATICS (STM) TEACHER - Muhammad, Rabi (Sokoto Educational Review, 2020)
The main thrust of the paper was to examine the concept of lifelong learning and its relevance in self relevance. It discussed the role of Science Technology and Mathematics (STM) teacher in enhancing lifelong learning by adopting students centred active teaching techniques that could improve students’ activeness and promote maximum retention of STM knowledge and makes learning real and applicable to life situation. It suggested that teachers should encourage students to see learning as an integral part of successful living.